Types of retention for implant-supported fixed prosthesis: a narrative literature review - Almeida-Mares, Clara; Metzker Lyra , Fernando Teodoro; Rocha Dias, Danilo; Santos Lages, Frederico (Revista Estomatología, 2022)
Background: The development of implant dentistry, along with implant-supported prostheses, made it possible to carry out functional and aesthetic rehabilitation treatments for patients, promoting comfort and durability in the results. For the achievement of the rehabilitation treatment, the choice of the retentive system of the prosthesis that best suits the patient's expectations, together with their clinical and radiographic conditions is essential.Objective: Perform a literature review addressing the main retention systems for fixed prostheses on implants, especially screwed and cemented, contextualizing them with new materials, components and techniques, guiding the decision-making of dental surgeons for their clinical planning.Materials and methods: A bibliographic search was performed on MEDLINE, Embase, Cochrane Library and SciElo platforms, filtering articles in Portuguese or English, with no date restriction until June 2, 2021.Conclusion: The choice of the retention system to be used involves several factors. A gold standard retention technique has not yet been established, due to the advantages and disadvantages of each. The choice of retention method must be made in conjunction with the patient and more clinical studies with longer follow-up are necessary to obtain more information.